Pasar dan penentuan harga dalam sistem ekonomi Islam: Adaptasi terhadap tantangan global kontemporer - Hidayat, Hikmalyansyah; Yunus, Muh. (Maliki Interdisciplinary Journal, 2025)
In the rapid era of globalization, the market mechanism and price determination in the Islamic economic system have gained increasing attention. Unlike conventional systems, Islamic economics is based on Sharia principles that prioritize justice, transparency, and social welfare. The market functions not only as a place for transactions but also as a social mechanism ensuring fairness for all parties involved. This study aims to examine how these Islamic economic principles can be adapted to address contemporary global challenges, including competition with conventional economic systems and technological advancements such as fintech. Through a conceptual analysis approach, this research explores the process of ethical and transparent price setting, as well as the efforts of Islamic economics to balance technological advancements with compliance to Sharia regulations. The findings show that, with a strong foundation in Sharia principles, Islamic economics can not only adapt to global changes but also offer sustainable and inclusive solutions. The potential of Islamic economics as a more ethical and just alternative becomes increasingly relevant in the complex dynamics of the global market.